Realistic Mathematics Education (RME): Implementation of Learning Models for Improving HOTS-Oriented Mathematics Problem-Solving Ability - Sri Sutarni; Antok Aryuana (AL-ISHLAH: Jurnal Pendidikan, 2023)
The results of students' still-inadequate capacity to solve mathematical problems with a focus on HOTS encouraged this study. The Realistic Mathematics Education (RME) learning model is one strategy for enhancing competence in this area. This research aims to determine whether or not eighth-graders at a State Junior High School in the Boyolali district of Central Java, Indonesia, can improve their problem-solving skills in mathematics by using the RME learning paradigm. Action research in the classroom is what we call it. Data is gathered through testing, observing, taking field notes, and documenting. Additionally, triangulation methods will be used to verify the accuracy of the data. Data was collected through both direct observation and standardised testing. Problem-solving indicator values, observation sheets, and recommendations for data interpretation are among the devices employed. The data analysis shows that teaching with the RME learning model improves students' capacity to solve mathematical problems. This is evidenced by the fact that all problem-solving indications have been met: There are four stages to any problem-solving process: 1) analysis, 2) planning, 3) execution, and 4) reflection (checking and interpreting).